A two-dimensional / three-dimensional organic-inorganic hybrid perovskite-derived formaldehyde gas-sensitive material and preparation method thereof
By designing the superimposed structure of two-dimensional/three-dimensional organic-inorganic hybrid perovskite materials, combined with its high stability and good light absorption performance, the problems of high temperature, humidity resistance and stability of traditional sensor materials are solved, and efficient and low-temperature detection of formaldehyde is achieved.
Patent Information
- Application Number
- CN202210372240.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-11
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-04-11
AI Technical Summary
Existing semiconductor sensors require a higher temperature when measuring formaldehyde, resulting in high power consumption and safety hazards in flammable or explosive environments. At the same time, three-dimensional perovskite materials are easily decomposed in humid, high temperature, oxygen and light environments, affecting their stability.
A two-dimensional/three-dimensional organic-inorganic hybrid perovskite-derived formaldehyde gas-sensitive material was designed. By constructing a two-dimensional/three-dimensional superposition structure A2BX4/ABX3, combining the high stability of two-dimensional perovskites and the good light absorption and carrier transport performance of three-dimensional perovskites, it forms a p-n heterojunction to improve gas-sensitive performance.
It effectively reduces the working temperature of the material and maintains a high response value in high humidity environments, significantly improves the gas-sensitive performance to formaldehyde, and solves the problems of high temperature, humidity resistance and stability of traditional sensor materials.
Smart Images

Figure CN114965593B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gas-sensitive elements, in particular to a two-dimensional / three-dimensional organic-inorganic hybrid perovskite-derived formaldehyde gas-sensitive material and a preparation method thereof. Background Art
[0002] Among the most common indoor air pollutants, formaldehyde is a colorless toxic gas that mainly comes from necessities such as interior decoration materials and furniture, which seriously affects people's health. Long-term exposure to a certain concentration of formaldehyde atmosphere can cause symptoms such as dry eyes, chest tightness, shortness of breath, and other types of physical discomfort. According to the World Health Organization (WHO) standard, the standard value of indoor formaldehyde is an average maximum concentration of no more than 0.08ppm within 30 minutes, so it is very necessary to develop a formaldehyde sensor with high sensitivity, high selectivity, and low detection limit.
[0003] Existing research shows that many sensors based on metal oxide semiconductors require relatively high temperatures when measuring formaldehyde. Among them, SnO2 is a very typical semiconductor gas-sensitive material with a simple synthesis method and excellent chemical stability. However, since its operating temperature is mostly high, the sensor not only consumes a lot of power at a high operating temperature, but also has safety hazards in flammable or explosive environments. Therefore, it is very necessary to reduce the operating temperature of semiconductor sensors.
[0004] There are many ways to reduce the operating temperature of semiconductor sensors. First, by compounding with narrow bandgap materials, the operating temperature can be effectively reduced through the transfer of excited electrons caused by light excitation or thermal activation. Second, by modifying its surface with precious metals such as Pd, Au, and Pt, it can play a catalytic role and improve gas sensitivity at lower operating temperatures.
[0005] Organic-inorganic hybrid three-dimensional perovskite ABX3 (A is an organic cation, B is a metal ion, and X is a halogen ion) is a narrow-bandgap material with good photoelectric properties, and therefore occupies a dominant position in the application of photovoltaics. In recent years, three-dimensional organic-inorganic hybrid perovskite materials have attracted widespread attention due to their excellent light absorption performance, high carrier mobility, and ultra-long diffusion of carriers, and people have gradually used them in the field of gas sensing.
[0006] However, the three-dimensional perovskite materials reported so far are very easy to decompose in a humid, high temperature, oxygen and light environment, which is not conducive to the long-term stable operation of the material in a complex environment. Especially in humid air with a relative humidity of more than 50%, the photosensitive components of the perovskite are rapidly degraded. Therefore, it is very necessary to improve the temperature and humidity stability of the perovskite material.
[0007] Two-dimensional perovskite A2BX4 (A is an organic cation, B is a metal ion, and X is a halogen ion) is formed by increasing the size of the organic ion at the A position, so that the cubic three-dimensional perovskite is cut along a specific direction to form a low-dimensional perovskite. Two-dimensional perovskites show better stability than three-dimensional perovskites because their organic components such as BA + (n-butylamine) is larger in size and smaller than organic ions such as MA + (methylamino), FA + (Carboxamidino) is more hydrophobic, so it has higher temperature and humidity stability. However, two-dimensional perovskites have problems such as large band gap, high exciton binding energy and poor charge transport, so they are limited in practical applications and are far inferior to three-dimensional perovskites.
[0008] Based on the above reasons, the present invention designs a two-dimensional / three-dimensional organic-inorganic hybrid perovskite-derived formaldehyde gas-sensitive material and a preparation method thereof, and constructs a two-dimensional / three-dimensional superimposed structure A2BX4 / ABX3. While combining the advantages of high stability of two-dimensional perovskite, the strong light absorption and good carrier transport properties of three-dimensional perovskite materials are utilized to further improve the material's gas-sensitive properties to formaldehyde. Summary of the invention
[0009] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a two-dimensional / three-dimensional organic-inorganic hybrid perovskite-derived formaldehyde gas-sensitive material and a preparation method thereof. The two-dimensional / three-dimensional superimposed structure combines the high stability of two-dimensional perovskite and utilizes the good light absorption and carrier transport properties of three-dimensional perovskite materials to further improve the formaldehyde gas-sensitive performance of the material.
[0010] In order to achieve the above object, the present invention provides a two-dimensional / three-dimensional organic-inorganic hybrid perovskite-derived formaldehyde gas-sensitive material and a preparation method thereof, comprising the following steps:
[0011] S1: Preparation of three-dimensional perovskite material FASnI3:
[0012] Place hydroiodic acid and hypophosphorous acid in a flask and mix them thoroughly, and introduce nitrogen to fill the flask with nitrogen. Place the flask in an oil bath and heat it to 135°C. Add SnI2 and stir until the solution turns bright yellow. Then add FAI and continue stirring. The molar ratio of FAI to SnI2 is 1:1. After cooling to room temperature, let it stand for 12 hours to obtain black crystals. Wash the crystals thoroughly with anhydrous ethanol. The obtained product is placed in a vacuum drying oven at 65°C for 24 hours.
[0013] S2: Preparation of two-dimensional perovskite material (BA) 2SnI4:
[0014] Place hydroiodic acid and hypophosphorous acid in a flask and mix them thoroughly. First, introduce nitrogen to fill the flask with nitrogen. Place the flask in an oil bath and heat it to 135°C. Add SnI2 and stir until the solution turns bright yellow. Then add BAI and continue stirring for 1 hour. The molar ratio of BAI to SnI2 is 1:1. After cooling to room temperature, let it stand for 12 hours to obtain black crystals. Wash the crystals thoroughly with anhydrous ether. The obtained product is placed in a vacuum drying oven at 65°C for 24 hours.
[0015] S3: Preparation of FASnI3 / (BA)2SnI4:
[0016] Place hydroiodic acid and hypophosphorous acid in a flask and mix them thoroughly. First, introduce nitrogen to fill the flask with nitrogen. Place the flask in an oil bath and heat it to 135°C. Add SnI2 and stir until the solution turns bright yellow. Then add FAI and BAI and continue stirring. Cool to room temperature and let stand for 12 hours to obtain black crystals. Wash the crystals thoroughly with anhydrous ether and place the product in a vacuum drying oven at 65°C for 24 hours.
[0017] S4: Preparation of FASnI3 / (BA)2SnI4 / SnO2:
[0018] A series of FASnI3 / (BA)2SnI4 samples were placed in a tube furnace and calcined at 210℃ in air atmosphere for 2 hours with a heating rate of 2℃ / min to decompose part of FASnI3 / (BA)2SnI4 into SnO2. The obtained composite material was defined as FA+XBA-S, where FA is FASnI3, BA is (BA)2SnI4, X is the molar percentage of (BA)2SnI4, and S is SnO2.
[0019] S5: Characterize the materials using XRD, TEM, XPS, BET, etc.
[0020] S6: Gas sensing performance test of FASnI3 / (BA)2SnI4 / SnO2:
[0021] Weigh the sample and terpineol and grind them thoroughly in an agate mortar to form a paste;
[0022] Apply the paste evenly on the ceramic tube and dry it under an infrared lamp for 2 hours;
[0023] The gas sensor covered with the material was placed in a porcelain boat and fired in a muffle furnace for 2 hours to accelerate the volatilization of terpineol;
[0024] A nickel-chromium alloy heating wire is inserted into the ceramic tube to control the operating temperature of the sensor, and the ceramic tube is welded to the six-hole base;
[0025] The component was aged at an operating temperature of 100°C for 7 days, and a gas-sensitivity test was performed when the component resistance tended to be stable.
[0026] Compared with the prior art, the present invention forms a pn heterojunction between the introduced (BA)2SnI4 and FASnI3 and SnO2, thereby accelerating the transfer of electrons between perovskite and SnO2. In addition, since (BA)2SnI4 contains a hydrophobic long alkyl chain, the introduced BA cation passivates the surface defects, thereby enhancing the phase stability and moisture resistance of the material, and can effectively reduce the working temperature of the material, and still maintain a high response value when the humidity is high, effectively improving the gas-sensitive performance of the material prepared by the present invention to formaldehyde. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The figure is a schematic diagram of the relationship between the response value of 50ppm formaldehyde gas and the operating temperature of the sensors made of FA-S, FA+5BA-S, FA+10BA-S, FA+15BA-S, FA+20BA-S and BA-S samples of the present invention (FA is FASnI3, BA is (BA)2SnI4, the number is the molar percentage of (BA)2SnI4, and S is SnO2) in an environment of relative humidity of 55%.
[0028] Figure 2 It is a schematic diagram of the response test of FA+10BA-S and FA-S of the present invention to 50 ppm formaldehyde, ethanol, acetone, methanol and benzene under the environment of 50° C. and relative humidity of 55%.
[0029] Figure 3 It is a schematic diagram of the dynamic response and recovery curve of FA+10BA-S and FA-S of the present invention to 50 ppm formaldehyde in an environment of 50° C. and a relative humidity of 55%.
[0030] Figure 4 The figure is a schematic diagram of the dynamic response of FA+10BA-S of the present invention to different concentrations of formaldehyde (0.5-50 ppm) under the environment of 50° C. and relative humidity of 55% and its fitting curve.
[0031] Figure 5 It is a schematic diagram of the repeatability and long-term stability test of FA+10BA-S of the present invention to 50 ppm formaldehyde under the environment of 50° C. and relative humidity of 55%.
[0032] Figure 6 Schematic diagram of the test of the influence of different relative humidity (RH) on the response value of FA+10BA-S and FA-S to 50 ppm formaldehyde at 50°C in the present invention.
[0033] Figure 7The response values of FA+10BA-S and FA-S of the present invention to 50 ppm formaldehyde were tested after exposure to different lengths of time in an environment of 50° C. and humidity of (a) 55±3% and (b) 78±3%. DETAILED DESCRIPTION
[0034] The present invention will now be further described with reference to the accompanying drawings.
[0035] See also Figures 1 to 7 The present invention provides a two-dimensional / three-dimensional organic-inorganic hybrid perovskite-derived formaldehyde gas-sensitive material and a preparation method thereof, comprising the following steps:
[0036] S1: Preparation of three-dimensional perovskite material FASnI3:
[0037] Place hydroiodic acid and hypophosphorous acid in a flask and mix them thoroughly, and introduce nitrogen to fill the flask with nitrogen. Place the flask in an oil bath and heat it to 135°C. Add SnI2 and stir until the solution turns bright yellow. Then add FAI and continue stirring. The molar ratio of FAI to SnI2 is 1:1. After cooling to room temperature, let it stand for 12 hours to obtain black crystals. Wash the crystals thoroughly with anhydrous ethanol. The obtained product is placed in a vacuum drying oven at 65°C for 24 hours.
[0038] S2: Preparation of two-dimensional perovskite material (BA) 2SnI4:
[0039] Place hydroiodic acid and hypophosphorous acid in a flask and mix them thoroughly. First, introduce nitrogen to fill the flask with nitrogen. Place the flask in an oil bath and heat it to 135°C. Add SnI2 and stir until the solution turns bright yellow. Then add BAI and continue stirring for 1 hour. The molar ratio of BAI to SnI2 is 1:1. After cooling to room temperature, let it stand for 12 hours to obtain black crystals. Wash the crystals thoroughly with anhydrous ether. The obtained product is placed in a vacuum drying oven at 65°C for 24 hours.
[0040] S3: Preparation of FASnI3 / (BA)2SnI4:
[0041] Place hydroiodic acid and hypophosphorous acid in a flask and mix them thoroughly. First, introduce nitrogen to fill the flask with nitrogen. Place the flask in an oil bath and heat it to 135°C. Add SnI2 and stir until the solution turns bright yellow. Then add FAI and BAI and continue stirring. Cool to room temperature and let stand for 12 hours to obtain black crystals. Wash the crystals thoroughly with anhydrous ether and place the product in a vacuum drying oven at 65°C for 24 hours.
[0042] S4: Preparation of FASnI3 / (BA)2SnI4 / SnO2:
[0043] A series of FASnI3 / (BA)2SnI4 samples were placed in a tube furnace and calcined at 210℃ in air atmosphere for 2 hours with a heating rate of 2℃ / min to decompose part of FASnI3 / (BA)2SnI4 into SnO2. The obtained composite material was defined as FA+XBA-S, where FA is FASnI3, BA is (BA)2SnI4, X is the molar percentage of (BA)2SnI4, and S is SnO2.
[0044] S5: Characterize the materials using XRD, TEM, XPS, BET, etc.
[0045] S6: Gas sensing performance test of FASnI3 / (BA)2SnI4 / SnO2:
[0046] Weigh the sample and terpineol and grind them thoroughly in an agate mortar to form a paste;
[0047] Apply the paste evenly on the ceramic tube and dry it under an infrared lamp for 2 hours;
[0048] The gas sensor covered with the material was placed in a porcelain boat and fired in a muffle furnace for 2 hours to accelerate the volatilization of terpineol;
[0049] A nickel-chromium alloy heating wire is inserted into the ceramic tube to control the operating temperature of the sensor, and the ceramic tube is welded to the six-hole base;
[0050] The component was aged at an operating temperature of 100°C for 7 days, and a gas-sensitivity test was performed when the component resistance tended to be stable.
[0051] Example:
[0052] Preparation of three-dimensional perovskite material FASnI3:
[0053] Place 8 mL of hydroiodic acid and 1 mL of hypophosphorous acid in a 150 mL three-necked flask and mix thoroughly. Pass nitrogen gas for 5 minutes to fill the flask with nitrogen. Place the flask in an oil bath and heat to 135°C. Add 372 mg of SnI2 and stir until the solution turns bright yellow. Add 172 mg of FAI and continue stirring for 1 hour (pass N2 continuously during the process). After cooling to room temperature, stand for 12 hours to obtain black crystals. Wash the crystals thoroughly with anhydrous ethanol, and place the resulting product in a vacuum drying oven at 65°C for 24 hours.
[0054] Preparation of two-dimensional perovskite material (BA) 2SnI4:
[0055] Place 6 mL of hydroiodic acid and 1.5 mL of hypophosphorous acid in a 150 mL three-necked flask and mix thoroughly. First, introduce nitrogen for 5 minutes to fill the flask with nitrogen. Place the flask in an oil bath and heat it to 120°C. Add 447 mg of SnI2 and stir until the solution turns bright yellow. Then add 483 mg of BAI- and continue stirring for 1 hour (continuously introduce N2 during the process). After cooling to room temperature, stand for 12 hours to obtain black crystals. Wash the crystals thoroughly with anhydrous ether, and place the resulting product in a vacuum drying oven at 65°C for 24 hours.
[0056] Preparation of FASnI3 / (BA)2SnI4:
[0057] Taking FA+5BA as an example, 8mL of hydroiodic acid and 1mL of hypophosphorous acid are placed in a 150mL three-necked flask and mixed thoroughly. First, nitrogen is introduced for 5 minutes to fill the flask with nitrogen. Place the flask in an oil bath and heat it to 135°C. Add 744mg of SnI2 and stir until the solution turns bright yellow. Then add 327mg of FAI and 40mg of BAI and continue stirring for 1 hour (N2 is continuously introduced during the process). After cooling to room temperature, black crystals can be obtained by standing for 12 hours. The crystals are fully washed with anhydrous ether, and the resulting product is placed in a vacuum drying oven at 65°C for 24 hours.
[0058] (The actual amount of FAI and BAI required for the preparation of FA+10BA, FA+15BA and FA+20BA can be calculated based on the molar percentage).
[0059] Preparation of FASnI3 / (BA)2SnI4 / SnO2:
[0060] A series of FASnI3 / (BA)2SnI4 samples were placed in a tube furnace and calcined at 210°C in air for 2 hours at a heating rate of 2°C / min to decompose part of FASnI3 / (BA)2SnI4 into SnO2. The resulting composite material is defined as FA+XBA-S, where FA is FASnI3, BA is (BA)2SnI4, X is the molar percentage of (BA)2SnI4, and S is SnO2.
[0061] Characterization of FASnI3 / (BA)2SnI4 / SnO2:
[0062] The materials were characterized by XRD, TEM, XPS, BET and other methods.
[0063] Gas sensing performance test of FASnI3 / (BA)2SnI4 / SnO2:
[0064] 1. First, weigh 20 mg of sample and 50 μL of pineneol and grind them thoroughly in an agate mortar to form a paste.
[0065] 2. Apply the paste evenly on the ceramic tube and dry it under infrared lamp for 2 hours.
[0066] 3. Place the gas sensor covered with the material into a ceramic boat and bake it at 200℃ in a muffle furnace for 2 hours to accelerate the volatilization of pine alcohol (baking operation can be omitted for ether solution adhesive). Insert the nickel-chromium alloy heating wire into the ceramic tube to control the working temperature of the sensor, and weld the ceramic tube to the six-hole base.
[0067] 4. Aging the component at an operating temperature of 100°C for 7 days, and performing a gas-sensitivity test when the component resistance tends to be stable.
[0068] like Figure 1 As shown in the figure, the relationship between the response value of the sensor made of FA-S, FA+5BA-S, FA+10BA-S, FA+15BA-S, FA+20BA-S and BA-S samples to 50ppm formaldehyde gas and the working temperature under the environment of relative humidity of 55% (25-140℃) (FA is FASnI3, BA is (BA)2SnI4, the number is the molar percentage of the substance, and S is SnO2)
[0069] In order to evaluate the effect of (BA)2SnI4 content in the FASnI3 / (BA)2SnI4 / SnO2 ternary system on the formaldehyde gas sensitivity, we compared the formaldehyde sensitivity properties of the calcined samples. Figure 1 It shows that the optimal working temperature of FA-S is 80℃, and the response value shows a downward trend when the working temperature further increases. Compared with the binary complex FA-S, the introduction of part of (BA)2SnI4 can significantly improve the response values of FA+5BA-S and FA+10BA-S to 50ppm formaldehyde at the same working temperature, and the optimal working temperature drops to 50℃. However, when the (BA)2SnI4 content is further increased, the sensitivity of FA+15BA-S and FA+20BA-S to formaldehyde at low temperatures decreases significantly. In addition, BA-S has the worst performance among all materials, and the FA+20BA-S with the highest (BA)2SnI4 content in the ternary system is very similar to the BA-S curve, and the response values are close to 1, indicating that the (BA)2SnI4 content is too high and is not suitable as a sensitive material for formaldehyde.
[0070] like Figure 2 As shown, the selectivity test of FA+10BA-S and FA-S for 50ppm formaldehyde, ethanol, acetone, methanol and benzene at 50℃ and 55% relative humidity
[0071] Figure 2It shows that under this condition, compared with FA-S, the introduction of (BA)2SnI4 makes the response value of FA+10BA-S at higher humidity comprehensively improved. This is because the two-dimensional perovskite effectively weakens the competition between water molecules and adsorbed oxygen. In addition, it can be seen from the figure that ethanol has a great interference with the low-temperature detection of formaldehyde by FA-S, but after the addition of (BA)2SnI4, the response value of formaldehyde is improved to a certain extent, thus solving the problem. This is related to the change in the adsorption energy of FA+10BA-S after doping. Therefore, it can be known that FA+10BA-S has good selectivity in the detection of formaldehyde at medium humidity and low temperature.
[0072] like Figure 3 As shown, the dynamic response and recovery curves of FA+10BA-S and FA-S to 50 ppm formaldehyde in an environment of 50°C and 55% relative humidity.
[0073] From the single-cycle response-recovery comparison of FA+10BA-S and FA-S to 50ppm formaldehyde at 50°C and 55% relative humidity, it can be seen that when formaldehyde gas is injected into the test chamber, both curves gradually rise and eventually tend to equilibrium, and when the components are exposed to the air again, the curves gradually return to their original state. Although the response speed of FA+10BA-S has not been significantly improved compared to FA-S (67s and 71s respectively), the response value of FA+10BA-S has increased by nearly two-thirds, and the recovery time has been shortened from 183s to 81s.
[0074] like Figure 4 As shown, the dynamic response of FA+10BA-S to different concentrations of formaldehyde (0.5-50ppm) at 50°C and 55% relative humidity and its fitting curve (inset)
[0075] Figure 4 The real-time dynamic response of the FA+10BA-S-based gas sensor to different concentrations of formaldehyde at 50°C and 55% relative humidity is demonstrated. The dynamic curve shows that as the formaldehyde concentration increases, the response value increases significantly and gradually, and when the equilibrium state is reached, the response value tends to a constant value with only some slight fluctuations. When the gas sensor is exposed to the air atmosphere again, the response value gradually decreases and eventually reaches the initial state.
[0076] like Figure 5 As shown, (a) repeatability test of FA+10BA-S for 50 ppm formaldehyde at 50°C and 55% relative humidity; (b) long-term stability test
[0077] Repeatability and stability are also important indicators for measuring the performance of gas sensors. Figure 5 (a) and Figure 5(b) shows the five continuous cycle response-recovery curves of the FA+10BA-S sensor to 50 ppm formaldehyde in an environment of 50°C and 55% relative humidity, as well as the long-term stability test graph of the response value within 30 days under the same test conditions. Figure 5 The response values of FA+10BA-S in (a) are all kept around 51.5, with the maximum deviation less than 2%, and the response / recovery time has no obvious change, which strongly proves that the sensor has good repeatability. Figure 5 (b) It can be seen that as the number of days increases, the response value of FA+10BA-S fluctuates slightly but still remains around 50, indicating that the sensor also has good stability.
[0078] like Figure 6 As shown, the effect of different relative humidity (RH) on the response value of FA+10BA-S and FA-S to 50 ppm formaldehyde at 50°C was tested.
[0079] When the operating temperature is low, the ambient humidity has a destructive effect on gas sensors. This problem has always been a research difficulty and hotspot in the field of sensing. Figure 6 , we took the response value measured at a relative humidity of 34% as the initial value 100%, and compared the changes in the response values of FA+10BA-S and FA-S sensors to 50ppm formaldehyde at different relative humidity at 50℃, in order to further study the effect of two-dimensional perovskite (BA)2SnI4 on improving the moisture resistance of the material. From the figure, we can see that when the relative humidity increases to 46%, the response value of FA-S decreases by about 23% compared with the initial value; and when the relative humidity further increases to 55%, the response value of FA-S drops sharply to 39.8%. The FA+10BA-S curve shows a different trend. When the relative humidity increases to 55%, the response value of FA+10BA-S decreases by only about 20% compared with the initial value; and when the relative humidity further increases to 78%, the response value of FA+10BA-S in the high humidity section still retains 50%, and the response value is about 30, and the detection signal at this time is still very significant. The results indicate that the introduced (BA)2SnI4 provides a "moisture-proof" effect to the composite and enhances its environmental stability due to its hydrophobic alkylammonium cation.
[0080] like Figure 7 As shown, the response values of FA+10BA-S and FA-S to 50 ppm formaldehyde after exposure to different lengths of time in an environment with a humidity of 55±3% at 50°C (a); and the response values of FA+10BA-S and FA-S to 50 ppm formaldehyde after exposure to different lengths of time in an environment with a humidity of 78±3%.
[0081] In order to compare the stability of FA+10BA-S and FA-S in medium and high humidity atmospheres, the newly manufactured components were exposed to environments with relative humidity of 55±3% and 78±3% for different lengths of time, and then the response values to 50ppm formaldehyde were tested at 50℃. Figure 7 (a) It can be seen that the response value of FA+10BA-S in a moderate humidity atmosphere is basically stable above 50, without significant changes, while FA-S decreases by one third under the same conditions. Figure 7 (b) It can be seen that after exposure to a high humidity atmosphere for 24 hours, the response value of FA+10BA-S is about 29.6, with only a slight decrease, while FA-S under the same conditions drops to 2.5. The trend of the two curves proves that the introduction of the two-dimensional perovskite (BA)2SnI4 improves the stability of FA+10BA-S under medium and high humidity.
[0082] The above are only preferred embodiments of the present invention, which are only used to help understand the method and core ideas of the present application. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
[0083] The present invention solves the problems of high operating temperature, poor moisture resistance, stability and the need for precious metal modification of formaldehyde sensor materials in the prior art as a whole. The material FASnI3 / (BA)2SnI4 / SnO2 obtained by combining two-dimensional / three-dimensional organic-inorganic hybrid perovskites and then calcining them can achieve rapid and efficient detection of formaldehyde in an environment of lower temperature and higher humidity, and has good market prospects.
Claims
1. A method for preparing a two-dimensional / three-dimensional organic-inorganic hybrid perovskite-derived formaldehyde gas-sensitive material, characterized in that: The following steps are involved: S1: Preparation of three-dimensional perovskite material FASnI3: Place hydroiodic acid and hypophosphorous acid in a flask and mix them thoroughly, and introduce nitrogen to fill the flask with nitrogen. Place the flask in an oil bath and heat it to 135°C. Add SnI2 and stir until the solution turns bright yellow. Then add FAI and continue stirring. The molar ratio of FAI to SnI2 is 1:
1. After cooling to room temperature, stand for 12 hours to obtain black crystals. Wash the crystals thoroughly with anhydrous ethanol. Place the obtained product in a vacuum drying oven at 65°C for 24 hours. S2: Preparation of two-dimensional perovskite material (BA) 2SnI4: Place hydroiodic acid and hypophosphorous acid in a flask and mix them thoroughly. First, introduce nitrogen to fill the flask with nitrogen. Place the flask in an oil bath and heat it to 135°C. Add SnI2 and stir until the solution turns bright yellow. Then add BAI and continue stirring for 1 hour. The molar ratio of BAI to SnI2 is 1:
1. After cooling to room temperature, stand for 12 hours to obtain black crystals. Wash the crystals thoroughly with anhydrous ether. Place the obtained product in a vacuum drying oven at 65°C for 24 hours. S3: Preparation of FASnI3 / (BA)2SnI4: Place hydroiodic acid and hypophosphorous acid in a flask and mix them thoroughly. First, introduce nitrogen to fill the flask with nitrogen. Place the flask in an oil bath and heat it to 135°C. Add SnI2 and stir until the solution turns bright yellow. Then add FAI and BAI and continue stirring. Cool to room temperature and let stand for 12 hours to obtain black crystals. Wash the crystals thoroughly with anhydrous ether. Place the obtained product in a vacuum drying oven at 65°C for 24 hours. S4: Preparation of FASnI3 / (BA)2SnI4 / SnO2: A series of FASnI3 / (BA)2SnI4 samples were placed in a tube furnace and calcined at 210℃ in air atmosphere for 2 hours with a heating rate of 2℃ / min to decompose part of FASnI3 / (BA)2SnI4 into SnO2. The obtained composite material was defined as FA+XBA-S, where FA is FASnI3, BA is (BA)2SnI4, X is the molar percentage of (BA)2SnI4, and S is SnO2. S5: Characterize the materials using XRD, TEM, XPS, BET, etc. S6: Gas sensing performance test of FASnI3 / (BA)2SnI4 / SnO2: Weigh the sample and terpineol and grind them thoroughly in an agate mortar to form a paste; Apply the paste evenly on the ceramic tube and dry it under an infrared lamp for 2 hours; The gas sensor covered with the material was placed in a porcelain boat and fired in a muffle furnace for 2 hours to accelerate the volatilization of terpineol; Insert the nickel-chromium alloy heating wire into the ceramic tube to control the working temperature of the sensor, and weld the ceramic tube to the six-hole base; age the element at an operating temperature of 100°C for 7 days, and perform a gas-sensing test when the element resistance tends to be stable.
Citation Information
Patent Citations
High-selectivity methanol gas-sensitive material as well as preparation method and application thereof
CN106770495A
Isopropanol gas-sensitive element based on ZnSnO3 nanospheres of perovskite structures and preparation method of element
CN110412086A